STRATEGI PENGAJARAN HADIST TENTANG MENUNTUT ILMU DI RA MASYITOH SINGKIR WONOSOBO - Susanti, Maulida Rahma; Fadhila, Kesuna Hilyati; Faisal, Vava Imam Agus (AL-QALAM: JURNAL KEPENDIDIKAN, 2024)
One of the important aspects that must be developed at an early age is the aspect of religion and morals. This aspect is expected to equip children with good character and personality so that these values can continue to be instilled in children until they grow up. One way to instill good character in children is through teaching the hadith of the Prophet SAW. One of the hadiths that need to be taught to early childhood is the hadith about studying so that children have the enthusiasm to become lifelong learners. However, to teach these hadiths about studying knowledge to early childhood, teachers need the right strategy so that children can understand, memorize, and even the values from these hadiths can be embedded in the child. The purpose of this study was to find out the strategy for teaching hadith about studying at RA Masyitoh Singkir Wonosobo. The method used in this research is descriptive qualitative. The subjects of this study were group A students, RA Masyitoh Singkir Wonosobo. This research data collection technique through interviews with class teachers, observation and documentation. The results of the study show that the strategy used by RA teacher Masyitoh Singkir Wonosobo in teaching hadiths about studying is through habituation, where the teacher reads the hadiths every morning, then the children imitate and memorize them, and an assessment is carried out on the same day.